Optimization of Ultra-Wideband LNA using a Single CRLH TL Cell Matching Circuit with Hybrid Genetic-Nelder Mead Algorithm - Karataev, T.; Gunes, F.; Demirel, S.; Belen, M. Ali (IEEE, 2015)
In this work, an optimization of an Ultra-Wideband Low-Noise Amplifier (LNA) using a single symmetric Composite Right/Left-Handed Transmission Line (CRLH TL) cell in the balanced condition is presented by hybrid Genetic and Nelder-Mead Algorithm (GA-NMA). The GA-NMA multi-objective optimization is implemented independently to determine LC parameters for the maximum power delivery considering optimum tradeoff between mismatching levels at the input and output port of the transistor for a predetermined noise figure provided that the balance condition and the optimal value of the transition frequency are ensured. Finally, the designed LNA is simulated using Sonnet simulator.
Keywords: Composite Right/Left-Handed Transmission Lines; Hybrid Genetic-Nelder Mead Algorithm; Low-Noise Amplifier; Optimization; Engineering